KAJIAN MASALAH PRE-PROJECT SELLING APARTEMEN THE ASPEN PEAK RESIDENCE (PUTUSAN NO. 390/PDT.G/2017/PN.JKT.SEL) - Sarah Anissa Rahmayanti; Anda Setiawati (Fakultas Hukum Universitas Trisakti, 2021)
The practice of pre-project selling is widely used by development actors by being tied to the PPJB. However, problems arose, especially PPJB violations which led to lawsuits in court. In this study, the authors question whether the pre-project selling that is bound by the PPJB is in accordance with the applicable legal provisions and whether the judge's considerations in decision No. 390/Pdt.G/2017/PN.Jkt.Sel which stated that the default developer was correct. To answer these problems, research was carried out using normative juridical research types based on secondary data and the nature of the research was analytical descriptive with inductive conclusions drawn. From the analysis that has been carried out, the results of the research show that there is a discrepancy between the pre-project selling of The Aspen Peak Residence Apartment and the requirements of Articles 42 and 43 of the UURS, especially the conditions for certainty over land rights and matters agreed upon. Then the judge's decision stating that the developer was in default, the decision was correct because the developer was proven to have committed a default or violated the obligation to hand over two units of The Aspen Peak Residence Apartment.